Hubungan Persepsi Masyarakat, Komunikasi Petugas Kesehatan Dan Dukungan Pemerintah Terhadap Implementasi Vaksin Covid-19 Di Puskesmas Cibinong Tahun 2022 - Sarwendah Sarwendah; Nining Arini; Rindu Rindu (Jurnal Pengabdian Ilmu Kesehatan, 2023)
Corona virus disease 2019 (Covid-19) is a viral disease that first appeared in the city of Wuhan in December 2019, one of the efforts to prevent the spread of the Covid-19 virus is by administering a vaccine. The purpose of this study was to analyzed the relationship between public perception, health worker communication, and government support with the implementation of Covid-19 vaccination at puskesmas Cibinong in 2022. This type of research was an analytic survey with a cross sectional approach. This research was conducted in June 2022─February 2023 at the puskesmas Cibinong. The population of this study where all people who had been given done the 2nd dose of Covid-19 vaccine aged over 18 years, namely in January─June 2022 as many as 1.189 doses. With this Slovin formula, this research sample was obtained, namely 300 respondents with the sampling technique used, namely purposive sampling. This study used the chi square statistical test using SPSS 22. Testing the validity and reliability of the questionnaire was carried out on 34 respondents who were estimated to have good insight and in accordance with the theme under study in January 2023. The results showed that community perception obtained a p-value was 0,007, health worker communication p-value was 0,487 and government support obtained a p-value was 0,477 (p-value< 0,05). This value states showed there was a significant relationship between community perception and the implementation of the Covid-19 vaccine, but there was no relationship between health worker communication and government support with the implementation of the Covid-19 vaccine. It is expected that the community will always be open and enthusiastic in health programs implemented such as vaccination programs.